2022
DOI: 10.1200/jco.21.01918
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Exposure and Discontinuation in the PALbociclib CoLlaborative Adjuvant Study of Palbociclib With Adjuvant Endocrine Therapy for Hormone Receptor–Positive/Human Epidermal Growth Factor Receptor 2–Negative Early Breast Cancer (PALLAS/AFT-05/ABCSG-42/BIG-14-03)

Abstract: PURPOSE The PALLAS study investigated whether the addition of palbociclib, an oral CDK4/6 inhibitor, to adjuvant endocrine therapy (ET) improves invasive disease-free survival (iDFS) in early hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) breast cancer. In this analysis, we evaluated palbociclib exposure and discontinuation in PALLAS. METHODS Patients with stage II-III HR+, HER2– disease were randomly assigned to 2 years of palbociclib with adjuvant ET versus ET alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…It is also conceivable that precisely because a CDK 4/6 inhibitor is now available in the adjuvant setting, some physicians and patients may decide against the use of chemotherapy. However, regular monitoring of toxicities is of utmost importance since patients that received the CDK 4/6 inhibitor palbociclib discontinued treatment in 27.2% of cases due to adverse effects in the PALLAS trial [ 27 ]. Hence, the implementation of care plans such as specially trained nurses is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable that precisely because a CDK 4/6 inhibitor is now available in the adjuvant setting, some physicians and patients may decide against the use of chemotherapy. However, regular monitoring of toxicities is of utmost importance since patients that received the CDK 4/6 inhibitor palbociclib discontinued treatment in 27.2% of cases due to adverse effects in the PALLAS trial [ 27 ]. Hence, the implementation of care plans such as specially trained nurses is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The 3‐year invasive DFS was 88·2% for palbociclib plus ET and 88.5% for ET alone (hazard ratio = 0.93 [95% CI = 0.76‐1.15]; log‐rank P = 0.51) [ 134 ]. Despite high discontinuation rates in PALLAS (42.2%), it was found that the lack of significant IDFS difference was not directly associated with inadequate palbociclib exposure [ 135 ]. The inconsistent results between MonarchE and PALLAS might be due to the disparity in the proportion of patients at high risk.…”
Section: Early Breast Cancer: Systemic Treatmentmentioning
confidence: 99%
“…In the PALLAS trial, 42.2% stopped palbociclib before two years of treatment were completed, out of which the majority, namely 27.2%, discontinued due to AEs. However, ET non-persistence rates did not differ between the two treatment arms [ 73 ]. Penelope-B confirmed discontinuation rates within one year of treatment with palbociclib.…”
Section: Impact On Patients’ Adherence and Quality Of Lifementioning
confidence: 99%